2013
DOI: 10.1182/blood-2012-09-455352
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory KIR/HLA incompatibility between sexual partners confers protection against HIV-1 transmission

Abstract: Key Points• HIV-1 transmission is influenced by the compatibility of sexual partners for two immune system genes, KIR and HLA.• KIR/HLA incompatibility likely allows alloreactive NK cells from the exposed partner to reject incoming cells from the HIV-1-infected partner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
50
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 51 publications
4
50
1
Order By: Relevance
“…Licensed (or unlicensed) human NK cells appear to be relevant to several clinical conditions and for adoptive immunotherapy (for recent examples, see refs. [38][39][40][41]. Of particular relevance, human NK cells with self-specific KIRs can be educated after BM transplantation in a manner related to the studies presented here (42), suggesting that relevant trans interactions between KIRs on NK cells and HLA class I on hematopoietic cells should be considered in the appropriate clinical context.…”
Section: Discussionmentioning
confidence: 99%
“…Licensed (or unlicensed) human NK cells appear to be relevant to several clinical conditions and for adoptive immunotherapy (for recent examples, see refs. [38][39][40][41]. Of particular relevance, human NK cells with self-specific KIRs can be educated after BM transplantation in a manner related to the studies presented here (42), suggesting that relevant trans interactions between KIRs on NK cells and HLA class I on hematopoietic cells should be considered in the appropriate clinical context.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Conversely, the "matched" combinations we tested consisted of recipient KIRs recognizing index HLAs regardless of recipient HLA, because recipient NK cells will be inhibited by index HLA regardless of whether they have been educated or not. Our analyses (see Table 2 in Jennes et al 1 ) showed that HIV-1 transmission and lack thereof correlated with 1 such matched combination (recipient KIR2DL3/KIR2DL3 with index HLA-C1/ C2) and 1 such missing self combination (recipient KIR2DL1 with HLA-C1/C2 and index HLA-C1/C1), respectively, both of which are diluted out in the regrouped analyses by Behrendt and Zaia.…”
mentioning
confidence: 56%
“…We appreciate the interest of Drs Behrendt and Zaia in our recent study of allogeneic killer cell immunoglobulin-like receptor (KIR)/HLA combinations in HIV-1 transmission, 1 and we are grateful for the opportunity to respond to their comments. Behrendt and Zaia reanalyzed our data by testing regrouped "missing ligand" combinations consisting of recipient partner KIRs lacking cognate index partner HLAs, reporting that they are not associated with HIV-1 transmission.…”
mentioning
confidence: 99%
“…Moreover, we caution that such an analysis must simultaneously evaluate individual inhibitory and activating KIRs (in the at-risk partner) together with corresponding HLA ligands (missing vs present in the index case), with appropriate adjustment of statistical significance for multiple hypothesis testing. 1 and we are grateful for the opportunity to respond to their comments. Behrendt and Zaia reanalyzed our data by testing regrouped "missing ligand" combinations consisting of recipient partner KIRs lacking cognate index partner HLAs, reporting that they are not associated with HIV-1 transmission.…”
mentioning
confidence: 99%
“…1 Studying couples with HIV-positive index case, the authors reported that 2 of many possible combinations of recipient inhibitory KIR, recipient HLA, and index HLA were associated (positively or inversely) with nontransmission of HIV to the partner. The authors also reported that in vitro killing of CD41 T cells from HIVinfected patients by natural killer (NK) cells of healthy individuals was enhanced by inhibitory KIR whose ligand was missing from target cells (usually accompanied by activating KIR 3DS1 with ligand Bw4 present in the target).…”
mentioning
confidence: 99%